Visualization of the Child, the Family and the Education in János Kömlei's "Szükségben segítő könyv" (Training and Practice : Journal of Educational Sciences, 2010)
In my study, I analized the book "Szükségben segítő könyv" about the perceptions of children and family. Texts were compared to contemporary lifestyle and educational consultants, that examined the broader context of the interpretation of stories and sentences. Despite of the fact that János Kömlei's book is not specifically a pedagogical work there is a lot of information about upbringing and teaching children. The stories according to the educational consultants emphasize the importance of educating children. The child appears as a value, its the parent's responsibility to ensure a proper education. In the light of Locke's sensualist doctrines the method of upbringing determines the child's life.